Muzara’ah Contract of Farmer Perspective - Khalishah Ulfah; Muryani Arsal (www.amertainstitute.com, 2023)
Muzara’ah profit-sharing is a system that involves an agreement between the landowner and the workers. This study aims to determine the implementation of the agreement between the landowner and the cultivator in the village of Bottopadang, District of Kahu. The research method used is a qualitative descriptive approach, with unstructured interview data collection techniques. The selection of respondents using purposive sampling with the number of respondents is 6 people as workers (farmers). The results showed that the sharing of muzara’ah profits that had occurred so far was carried out verbally, and generally the profit-sharing was carried out based on the agreement between the landowner and the workers with a proportion of 1/3 for the landowner and 2/3 for the workers, and even sometimes all the harvest was given to workers if the amount of crop was small. The application of muzara'ah has created trust, attitude of helping each other between the landowners and workers and helping the community's economy in the Bottopadang village